Mathematical Literacy Ability Reviewed from Cognitive Style of Students on Double Loop Problem Solving Model with RME Approach - Fajriyah, Euis; Mulyono, Mulyono; Asikin, M. (Universitas Negeri Semarang, 2019)
Mathematical literacy ability and students cognitive styles play important role in mathematics learning. The purpose of this study was to know the quality of learning and mathematical literacy ability reviewed from the students' cognitive style in learning by using Double Loop Problem Solving model with the RME approach. This study conducted on VIII grade students of SMP Negeri 40 Semarang in the academic year of 2017/ 2018. This study applied a mixed method with concurrent embedded designs. The results of the study showed that learning by using Double Loop Problem Solving model with RME approach on students' mathematics literacy abilities is good qualified. Students with reflective cognitive style were able to master communication, mathematizing, reasoning and argumentation, and devising strategies for solving problems very well, the components of representation, using symbolic, formal, and technical language and operation, and using mathematics tools were quite well mastered. Students with impulsive cognitive style were able to master communication very well, the components of mathematizing, reasoning and argumentation, representation, devising strategies for solving problems, using symbolic, formal, and technical language and operation, were quite well mastered, and the component of using mathematical tools, have not been able to be mastered. Students with fast accurate cognitive style were able to master communication, mathematizing, representation, devising strategies for solving problems, using symbolic, formal, and technical language and operation, and using mathematics tools very well, the component of reasoning and argumentation were quite well mastered. Students with slow-inaccurate cognitive style were quite well to master communication, mathematizing, reasoning and argumentation, devising strategies for solving problems, and using symbolic, formal, and technical language and operation, the components of representation and using mathematics tools have not been able to be mastered.